SOCIAL MOVEMENT FOR HEALTH: AN INNOVATIVE MODEL OF COMMUNITY SERVICE IN THE DIGITAL AGE - Hutapea, Dwight Mahaputera Marulitua; Hutapea , Lyna M. N. (MSJ : Majority Science Journal, 2025)
Abstract This article analyzes how digital transformation reshapes social movements for health in Indonesia by introducing innovative community engagement models supported by online platforms and participatory technologies. Using a mixed-method approach that integrates conceptual analysis with secondary data from digital adoption surveys and public health reports, the study identifies key digital mechanisms including micro-campaigns, digital volunteerism networks, telehealth collaborations, crowdfunding ecosystems, and digital health literacy programs. These models expand community participation, accelerate information dissemination, and enhance public responsiveness during health crises. The findings also highlight structural challenges, including inequitable digital access, misinformation, sustainability gaps, and limited institutional coordination. To address these constraints, the article proposes a strategic framework emphasizing inclusive digital infrastructure, strengthened health literacy, multi-stakeholder collaboration, ethical data governance, and continuous research-based innovation. Overall, the study contributes a comprehensive understanding of how digital ecosystems can support sustainable, citizen-driven health engagement and improve public health outcomes in the digital era